Nereson 2010 Sedimentation Rates in the Distal Basin of Arctic Proglacial Linnévatnet, Western Spitsbergen, Svalbard: Evidence from Radioactive Fallout Cesium-137 - ACADIS Community Support (Arctic Data Center, 2013)
Abstract: The rhythmically laminated sediments found in proglacial Linnévatnet in western Spitsbergen, Svalbard may be suitable for the reconstruction of paleoenvironmental conditions such as temperature, precipitation, and glacier mass balance. In order to use these sediments as a proxy for past environmental change, however, we must understand which modern environmental factors contribute to Linnévatnet’s patterned sediments. The goal of this study is to further that understanding by estimating the rate of sedimentation in Linnévatnet’s distal basin over a period for which climatic conditions are well constrained (1963-2009). Average estimates for the sedimentation rate were calculated using concentrations of fallout 137-Cs in two sediment cores (GC09-1 and GC09-2). Results from both coresindicate average sedimentation rates of 0.49 and 0.64 mm/yr, respectively, over the last half-century. The estimated sedimentation rates presented here are similar, but typically lower, than those put forth by previous workers who used varve counts, paleomagnetic methods, and sediment traps to quantify sedimentation rates over the same period. The evidence from this study for low sedimentation rates in Linnévatnet’s distal basin (<1mm/yr) implies that some recent years are poorly recorded by the archetypical annual silt-clay couplet, or varve. In the future, annual sedimentation patterns may be more accurately resolved by comparing varve counts to 137-Cs profiles that have been measured on the same core or series of cores.